Increasing Awareness of Health Protocols During Covid-19 Pandemic At SDN Setiamulya - Meiliana Nurfitriani; Budi Hendrawan; Mohammad Fahmi Nugraha; Yopa Taufik Saleh; Devi Annisa Rahmawati; Teti Nurul Fathiyati; Eki Hilman Rasyid; Gumgum Gumilar; Ismail Ismail (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This Community Partnership Program (PKM) aims to increase primary students’ understanding of the dangers of Covid 19 and educate them on how to prevent it through correct health protocols and being able to implement a healthy lifestyle. The targets of this program are high grade of primary students, namely grade 4, grade 5, and grade 6. The method used in this education is storytelling in an interactive online style via zoom platform. Stories are conveyed in English with simple language and sentences to make them easier to understand, besides that the delivery is combined with Indonesian so that children understand the meaning and are able to imitate certain sentences and movements well. The implementation of this program makes students enthusiastic and excited, especially using English. The students feel cooler when they listen to stories and speak English. Children enthusiastically mimic, sing and perform healthy protocol movements in interesting ways. Thus, children are able to understand the contents of the stories and values ??that are conveyed, so that they are able to apply them to new good habits in the era of new normal life. As conclusion, the storytelling method is able to provide a good understanding of the Covid 19 pandemic for children, so that awareness emerges to apply health protocols in their daily life